Anatomy and cytology of Taphrina entomospora during infection of Nothofagus - Hansen, Paula Veronica (2007)
Taphrina entomospora is one of the few species of the genus described on native plants of the Southern Hemisphere and also one of the few leaf pathogens known on Nothofagus species. The anatomical changes it produces on N. pumilio leaves, and its morphology, cytology, and sporogenesis were studied. The fungus is a perennial species that overwinters as mycelium in the foliar buds and infects the developing leaves, so the whole blade develops the disease symptoms. Interveinal areas of the leaves become chlorotic, thickened and rounded. Palisade parenchyma fails to develop, with spongy parenchyma developing as packed, rounded, isodiametric cells with little intercellular space. The mycelium is subcuticular, dikaryotic, and produces ascogenous hyphae, asci, and ascospores as described for other species in the genus. Before ascus discharge, ascospores bud in a regular, unique way. The life-cycle of T. entomospora is compared with other representative taxa in the genus and the distribution of this pathogen is discussed.